Circular RNA TFO as antiviral therapy against feline infectious peritonitis virus - Choong, Oi Kuan; Harun, Mohammad Syamsul Reza; Tejo, Bimo Ario; Omar, Abdul Rahman (2012)
Feline Infectious Peritonitis Virus (FIPV) is a feline coronavirus (FCoV) which causes a fatal immune-mediated disease called Feline Infectious Peritonitis (FIP) in cats. Antiviral treatments using Ribavirin and interferons have been used to treat the disease symptomatically. However, these treatments are ineffective. Furthermore, vaccine is ineffective to control FIP in cats. RNA based molecular therapy such as siRNA, miRNA and RNA aptamers have been studied against various infectious diseases and cancers. Little is known on the potential of Triple Helix-Forming Oligonucleotide (TFO) RNA as anti-viral therapy. Hence, TFO based RNA therapy is chosen as a molecular therapy to inhibit FIPV replication. Five sets of FIPV specific circular TFO RNA (TFO1 to TFO5) targeting the selected regions of virulent FIPV were designed and tested in vitro. The antiviral effect of circular TFOs was determined using cell culture and qRT-PCR assays. The results showed that all the circular TFO RNA, except for TFO2 RNA, significantly inhibited FIPV replication by reducing the viral RNA copy numbers up to 100,000 fold compared to control cells. In addition, circular TFO RNA with antiviral activity showed strong binding kinetics with a Kd of ~ 0.1μM. Hence, all the circular TFO except for TFO2 demonstrated antiviral effect on FIPV. This study describes the potential use of TFO as antiviral agent against coronavirus, FIPV in cats.